Bacterial signal transduction by cyclic Di-GMP and other nucleotide second messengers - Hengge,R; Gruendling,A; Jenal,U; Ryan,R; Yildiz,F (Journal of Bacteriology, 2015)
The first International Symposium on c-Di-GMP Signaling in Bacteria (22 to 25 March 2015, Harnack-Haus, Berlin, Germany) brought together 131 molecular microbiologists from 17 countries to discuss recent progress in our knowledge of bacterial nucleotide second messenger signaling. While the focus was on signal input, synthesis, degradation, and the striking diversity of the modes of action of the current second messenger paradigm, i.e., cyclic di-GMP (c-di-GMP), “classics” like cAMP and (p)ppGpp were also presented, in novel facets, and more recent “newcomers,” such as c-di-AMP and c-AMP-GMP, made an impressive appearance. A number of clear trends emerged during the 30 talks, on the 71 posters, and in the lively discussions, including (i) c-di-GMP control of the activities of various ATPases and phosphorylation cascades, (ii) extensive cross talk between c-di-GMP and other nucleotide second messenger signaling pathways, and (iii) a stunning number of novel effectors for nucleotide second messengers that surprisingly include some long-known master regulators of developmental pathways. Overall, the conference made it amply clear that second messenger signaling is currently one of the most dynamic fields within molecular microbiology, with major impacts in research fields ranging from human health to microbial ecology.